Toxicity of Military Smokes and Obscurants: Volume 1 - National Research Council (The National Academies Press, 1997)
Keywords: Environment and Environmental Studies; Conflict and Security Issues

Dietary Reference Intakes for Calcium, Phosphorus, Magnesium, Vitamin D, and Fluoride - Institute of Medicine (The National Academies Press, 1997)
Since 1941, Recommended Dietary Allowances (RDAs) has been recognized as the most authoritative source of information on nutrient levels for healthy people. Since publication of the 10th edition in 1989, there has been rising awareness of the impact of nutrition on chronic disease. In light of new research findings and a growing public focus on nutrition and health, the expert panel responsible for formulation RDAs reviewed and expanded its approach—the result: Dietary Reference Intakes. This new series of references greatly extends the scope and application of previous nutrient guidelines. For each nutrient the book presents what is known about how the nutrient functions in the human body, what the best method is to determine its requirements, which factors (caffeine or exercise, for example) may affect how it works, and how the nutrient may be related to chronic disease. The first volume of Dietary Reference Intakes includes calcium, phosphorus, magnesium, vitamin D, and fluoride. The second book in the series presents information about thiamin, riboflavin, niacin, vitamin B6, folate, vitamin B12, pantothenic acid, biotin, and choline. Based on analysis of nutrient metabolism in humans and data on intakes in the U.S. population, the committee recommends intakes for each age group—from the first days of life through childhood, sexual maturity, midlife, and the later years. Recommendations for pregnancy and lactation also are made, and the book identifies when intake of a nutrient may be too much. Representing a new paradigm for the nutrition community, Dietary Reference Intakes encompasses: Estimated Average Requirements (EARs). These are used to set Recommended Dietary Allowances. Recommended Dietary Allowances (RDAs). Intakes that meet the RDA are likely to meet the nutrient requirement of nearly all individuals in a life-stage and gender group. Adequate Intakes (AIs). These are used instead of RDAs when an EAR cannot be calculated. Both the RDA and the AI may be used as goals for individual intake. Tolerable Upper Intake Levels (ULs). Intakes below the UL are unlikely to pose risks of adverse health effects in healthy people. This new framework encompasses both essential nutrients and other food components thought to pay a role in health, such as dietary fiber. It incorporates functional endpoints and examines the relationship between dose and response in determining adequacy and the hazards of excess intake for each nutrient.
Keywords: Food and Nutrition

The Dynamics of Sedimentary Basins - National Research Council (The National Academies Press, 1997)
Keywords: Earth Sciences

Striking a Balance: Improving Stewardship of Marine Areas (The National Academies Press, 1997)
America's ocean and coastal regions—which provide wildlife habitat, commercial fish stocks, mineral reserves, travelways, recreation, and more—are under increasing pressure as more and more people exploit marine resources, leaving environmental damage in their wake. Striking a Balance responds to the urgency for sound decision-making in the management of marine resources. An expert committee proposes principles, goals, and a framework for marine area governance, including new governance structures at the federal and regional levels and improvements for existing governing and regulatory systems. Recommendations include using tools—such as zoning and liability—for resolving conflicts between users, controlling access to marine resources, and enforcing regulations. The book describes the wide-ranging nature and value of marine resources, evaluates their current management, and explores three in-depth case studies. It also touches on the implications of newer, more flexible, less hierarchical approaches to organizational behavior. Striking a Balance will be of interest to everyone concerned about marine resource management, especially federal and state marine managers and regulators, marine scientists and policy analysts, companies and organizations with interests in marine and coastal resources, and advocacy groups.
Keywords: Earth Sciences

Emerging Technologies for Nutrition Research: Potential for Assessing Military Performance Capability - Institute of Medicine (The National Academies Press, 1997)
The latest of a series of publications based on workshops sponsored by the Committee on Military Nutrition Research, this book's focus on emerging technologies for nutrition research arose from a concern among scientists at the U.S. Army Research Institute of Environmental Medicine that traditional nutrition research, using standard techniques, centered more on complex issues of the maintenance or enhancement of performance, and might not be sufficiently substantive either to measure changes in performance or to predict the effects on performance of stresses soldiers commonly experience in operational environments. The committee's task was to identify and evaluate new technologies to determine whether they could help resolve important issues in military nutrition research. The book contains the committee's summary and recommendations as well as individually authored chapters based on presentations at a 1995 workshop. Other chapters cover techniques of body composition assessment, tracer techniques for the study of metabolism, ambulatory techniques for the determination of energy expenditure, molecular and cellular approaches to nutrition, the assessment of immune function, and functional and behavioral measures of nutritional status.
Keywords: Food and Nutrition; Health and Medicine

Mars Sample Return: Issues and Recommendations - National Research Council (The National Academies Press, 1997)
The Space Studies Board of the National Research Council (NRC) serves as the primary adviser to the National Aeronautics and Space Administration (NASA) on planetary protection policy, the purpose of which is to preserve conditions for future biological and organic exploration of planets and other solar system objects and to protect Earth and its biosphere from potential extraterrestrial sources of contamination. In October 1995 the NRC received a letter from NASA requesting that the Space Studies Board examine and provide advice on planetary protection issues related to possible sample-return missions to near-Earth solar system bodies.
Keywords: Space and Aeronautics

Vitamin C Fortification of Food Aid Commodities: Final Report - Institute of Medicine (The National Academies Press, 1997)
Keywords: Food and Nutrition

The Industrial Green Game: Implications for Environmental Design and Management - National Academy of Engineering (The National Academies Press, 1997)
Industrial ecology is a concept that has emerged in response to growing public concern about the impact of industry on the environment. In this framework the natural flow (or circulation) of materials and energy that takes place in biological ecosystems becomes a model for more efficient industrial "metabolism." What industrial ecology is and how it may be applied to corporate environmentalism are the subject of The Industrial Green Game. This volume examines industrial circulation of materials, energy efficiency strategies, "green" accounting, life-cycle analysis, and other approaches for preventing pollution and improving performance. Corporate leaders report firsthand on "green" efforts at Ciba-Geigy, Volvo, Kennecott, and Norsk Hydro. And an update is provided on the award-winning industrial symbiosis project in Kalundborg, Denmark. The Industrial Green Game looks at issues of special concern to business, such as measuring and shaping public perceptions and marketing "green" products to consumers. It offers discussions of the appropriate roles of government and private business.
Keywords: Environment and Environmental Studies; Industry and Labor

Nonconventional Concrete Technologies: Renewal of the Highway Infrastructure - National Research Council (The National Academies Press, 1997)
Nonconventional Concrete Technologies: Renewal of the Highway Infrastructure identifies research and development opportunities in innovative, nonconventional materials and processes that have the potential to accelerate the construction process, improve the durability of highway pavement and bridges, and enhance the serviceability and longevity of new construction under adverse conditions.
Keywords: Engineering and Technology; Transportation and Infrastructure

The Role of Chromium in Animal Nutrition - National Research Council (The National Academies Press, 1997)
The American feed industry manufactures tons of dietary supplements and additives each year for inclusion in the diets of food-producing animals. Some scientists have suggested that chromium should be a key ingredient in nutritional supplements. Controversy exists, however, over whether chromium sources should be approved as feed additives and whether enough data exist to establish dietary requirements. Chromium use has been suggested to have positive impacts on farm profitability, and many animal health benefits have been attributed to chromium supplementation, including increased longevity; enhanced reproduction; decreased incidence of metabolic disorders, stress effects, and disease; reduced need for antibiotic usage; improved immune response; and lean carcass quality. This book addresses recent research on chromium in animal diets; metabolic interactions between chromium and other nutrients; assessments of form and species interactions; supplementation effects; bioavailability of chromium forms and sources; and effects of diet composition, stressors, and animal physiological status on chromium utilization. It also provides recommendations on the essentiality of dietary chromium in domestic animal species and guidelines for use of dietary chromium.
Keywords: Agriculture

Barrier Technologies for Environmental Management: Summary of a Workshop - National Research Council (The National Academies Press, 1997)
To control the migration of radioactive and hazardous wastes currently contained underground, barriers made of natural materials and man-made substances are constructed atop, and possibly around, the contaminated area. Barrier Technologies for Environmental Management provides a brief summary of the key issues that arose during the Workshop on Barriers for Long-Term Isolation. Recurring themes from the session include the importance of quality control during installation, followed by periodic inspection, maintenance, and monitoring, and documentation of installation and performance data. The book includes papers by the workshop presenters.
Keywords: Environment and Environmental Studies

Innovations in Ground Water and Soil Cleanup: From Concept to Commercialization - National Research Council (The National Academies Press, 1997)
Most books on ground water and soil cleanup address only the technologies themselves—not why new technologies are or are not developed. Innovations in Ground Water and Soil Cleanup takes a holistic approach to the entire field, addressing both the sluggish commercial development of ground water and soil cleanup technologies and the attributes of specific technologies. It warns that, despite cleanup expenditures of nearly $10 billion a year, the technologies remain rudimentary. This engaging book focuses on the failure of regulatory policy to link cleanup with the financial interests of the company responsible for the contamination. The committee explores why the market for remediation technology is uniquely lacking in economic drivers and why demand for innovation has been so much weaker than predicted. The volume explores how to evaluate the performance of cleanup technologies from the points of view of the public, regulators, cleanup entrepreneurs, and other stakeholders. The committee discusses approaches to standardizing performance testing, so that choosing a technology for a given site can be more timely and less contentious. Following up on Alternatives for Ground Water Cleanup (NRC, 1994), this sequel presents the state of the art in the cleanup of various types of ground water and soil contaminants. Strategies for making valid cost comparisons also are reviewed.
Keywords: Environment and Environmental Studies

Implementation Challenges for High-Temperature Composites - Anthony G. Evans (The National Academies Press, 1997)
Keywords: Engineering and Technology

Biographical Memoirs: Volume 71 - National Academy of Sciences (The National Academies Press, 1997)
Biographic Memoirs: Volume 71 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Pharmacokinetics and Drug Interactions in the Elderly and Special Issues in Elderly African-American Populations: Workshop Summary - Institute of Medicine (The National Academies Press, 1997)
Reports in the popular press about the increasing longevity of Americans and the aging of the baby boom generation are constant reminders that the American population is becoming older. Consequently, an issue of growing medical, health policy, and social concern is the appropriate and rational use of medications by the elderly. Although becoming older does not necessarily correlate with increasing illness, aging is associated with anatomical and physiological changes that affect how medications are metabolized by the body. Furthermore, aging is often related to an increased frequency of chronic illness (often combined with multiple health problems) and an increased use of medications. Thus, a better understanding of the absorption, distribution, metabolism, and excretion of drugs; of the physiologic responses to those medications; as well as of the interactions among multiple medications is crucial for improving the health of older people.
Keywords: Health and Medicine

(NAS Colloquium) Carbon Dioxide and Climate Change (The National Academies Press, 1997)
Keywords: Environment and Environmental Studies; Earth Sciences

Evaluation of the U.S. Department of Energy's Alternatives for the Removal and Disposition of Molten Salt Reactor Experiment Fluoride Salts - National Research Council (The National Academies Press, 1997)
This book discusses the technical alternatives for cleanup of radioactive fluoride salts that were the fuel for the Molten Salt Reactor Experiment, a novel nuclear reactor design that was tested in the 1960s at the Oak Ridge National Laboratory in Tennessee. These fluoride salts pose an unusual cleanup challenge. The book discusses alternatives for processing and removing the salts based on present knowledge of fluoride salt chemistry and nuclear reactions of the radioactive constituents.
Keywords: Environment and Environmental Studies

Lessons Learned from the Clementine Mission - National Research Council (The National Academies Press, 1997)
Keywords: Space and Aeronautics

Racial and Ethnic Differences in the Health of Older Americans - National Research Council (The National Academies Press, 1997)
Older Americans, even the oldest, can now expect to live years longer than those who reached the same ages even a few decades ago. Although survival has improved for all racial and ethnic groups, strong differences persist, both in life expectancy and in the causes of disability and death at older ages. This book examines trends in mortality rates and selected causes of disability (cardiovascular disease, dementia) for older people of different racial and ethnic groups. The determinants of these trends and differences are also investigated, including differences in access to health care and experiences in early life, diet, health behaviors, genetic background, social class, wealth and income. Groups often neglected in analyses of national data, such as the elderly Hispanic and Asian Americans of different origin and immigrant generations, are compared. The volume provides understanding of research bearing on the health status and survival of the fastest-growing segment of the American population.
Keywords: Behavioral and Social Sciences; Health and Medicine

In Her Own Right: The Institute of Medicine's Guide to Women's Health Issues - Institute of Medicine (The National Academies Press, 1997)
Right to life. Right to choice. Masectomy, lumpectomy. Vitamin therapy, hormone therapy, aromatherapy. Tabloids, op-eds, Phil, Sally, Oprah. Yesterday, women confided in their doctors about health problems and received private, albeit sometimes paternalistic, attention. Today, women's health issues are headline material. Topics that once raised a blush now raise a blare of conflicting medical news and political advocacy. Women welcome the new recognition of their health concerns. Now women are less often treated, as the old saw goes, as "a uterus with a person attached." At the same time, they need help in sorting through the flood of reports on scientific studies, claims of success for new treatments, and just plain myths. The Institute of Medicine (IOM) has responded to this need with In Her Own Right. Throughout its 25-year history, the IOM has provided authoritative views on fast-moving developments in medicine—bringing accuracy, objectivity, and balance to the hottest controversies. Talented science writer Beryl Lieff Benderly synthesizes this expertise into a readable overview of women's health. Why do women live longer than men? Why do more women than men suffer vertebral fractures? Benderly highlights what we know about the health differences between men and women and the mysteries that remain to be solved. With a frank, conversational approach, Benderly examines women's health across the life span: Issues of female childhood, adolescence, and sexual maturity, including smoking, eating behavior, teen pregnancy, and more. The host of issues surrounding the reproductive years; contraception, infertility, abortion, pregnancy and birth, AIDS, and mental health. Postmenopausal life and issues of aging, as health choices made decades earlier come home to roost. Benderly addresses women's experience with the nation's health care establishment and the controversy over the lack of female representation in the world of scientific research. Much more than a how-to guide, In Her Own Right translates the finest scholarship on topics of women's health into terms that will help any woman ask the right questions and make the right choices. Covering the spectrum from traditional beliefs to cutting-edge research, this book presents the personal insights of leading investigators, along with clear explanations of breakthrough studies written in plain English.
Keywords: Health and Medicine